Morules and morule-like features associated with carcinomas in various organs: report with immunohistochemical and molecular studies. Issue 1 (4th January 2006) - Makishi, S; Kinjo, T; Sawada, S; Chinen, K; Hirayasu, T; Hamada, T; Saito, K; Iwamasa, T
Abstract : Background: Morules have been reported in pulmonary blastoma (PB), well differentiated fetal adenocarcinoma of the lung (WDFA), and uterine endometrioid carcinoma (EC), and rarely in other carcinomas. β Catenin gene mutation has been associated with morule formation. Aims: To compare and clarify the cellular characteristics of morules in carcinomas in various organs and show that morules are distinct from epithelial cellular nodules. Methods: Twenty tumours were studied: two PBs, three WDFAs, three papillary lung adenocarcinomas, 11 ECs, and one papillary thyroid carcinoma. Numerous epithelial cell, oncofetal, and neuropeptide antibodies were used for immunohistochemistry. β Catenin gene mutation was investigated. Results: Morules in PBs and ECs were uniform cell clusters distinct from squamous differentiation. All were immunonegative for epithelial cell and oncofetal antigens, but those in ECs were positive for neurone specific enolase γ (NSEγ). Synaptophysin, encephalin, and somatostatin were sporadically immunopositive in PB morules. Morules were not seen in the other carcinomas and WDFAs, although morule-like features closely resembling morules histopathologically were seen. These were positive for epithelial cell and oncofetal antigens, and showed squamous differentiation. Their nuclei were more atypical and slightly larger than those in morules. Morule-like features were seen in WDFAs. β Catenin gene mutation was demonstrated in one EC and PB, and in two WDFAs. Conclusion: Morules were non-epithelial cell clusters showing neuronal differentiation. There were two types: endometrioid type, expressing NSEγ, and blastoma type, expressing neuropeptides. In contrast, similar morule-like features were epithelial nodules. Although the number of cases was small, the presence of morules showed no clear prognostic correlations.